1985
DOI: 10.1007/bf02534237
|View full text |Cite
|
Sign up to set email alerts
|

The Di‐ and triesters of the lipids of steer and human meibomian glands

Abstract: Three groups of diesters have been isolated and identified in the lipids of steer meibomian glands. The first group, designated as alpha Type I, with the abbreviated formula FA-alpha OHFA-FAlc, consisted of alpha-hydroxy fatty acids esterified to fatty acids and fatty alcohols in the approximate molar ratio 1:1:1. The second group, designated as omega Type I-St, with the abbreviated formula FA-omega OHFA-St, consisted of omega-hydroxy fatty acids esterified to fatty acids and sterols in the approximate molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 21 publications
2
78
2
Order By: Relevance
“…These results confi rmed independent observations from a number of research laboratories on the presence of large amounts of CEs and WEs in human meibum (18)(19)(20)(21)(22)(23). However, we could not concur on the reported fi ndings on oleamide ( 24 ), Cer, and other typical polar lipids ( 25,26 ).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These results confi rmed independent observations from a number of research laboratories on the presence of large amounts of CEs and WEs in human meibum (18)(19)(20)(21)(22)(23). However, we could not concur on the reported fi ndings on oleamide ( 24 ), Cer, and other typical polar lipids ( 25,26 ).…”
Section: Discussionsupporting
confidence: 72%
“…This was a clear sign of the presence of at least two isobaric compounds in the mixture. We hypothesized that these novel compounds might be related to the relatively poorly characterized families of di-and triesters of various kinds postulated by Nicolaides and Santos ( 19 ), specifi cally, the (O-acyl)--hydroxy FA (OAHFA) peroxyacetic acid as described in Materials and Methods. Then, both treated and untreated samples were analyzed by HPLC-MS side by side.…”
Section: Epoxides Of Wax Estersmentioning
confidence: 99%
“…For example, it has been reported that there are some 30 000 different lipid molecular species just in the human meibum (tear gland) [19]! Cell membranes are composed, in part, of at least hundreds, perhaps thousands, of different lipids.…”
Section: Role Of Cholesterol In Lipid Raftsmentioning
confidence: 99%
“…Investigation of the vanishingly small quantity of lipid in human tear film presents a unique challenge for study, and a range of analytical approaches have been applied to quantify the lipids in both tears and meibum 8,9 . A comprehensive overview of the molecular lipid composition of human tears has recently been realized through application of contemporary mass-spectrometric analytical tools [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%